Bactericidal, Antioxidant Activity and In Silico Analysis of Phytochemicals Derived From Selected Plants of Solanaceae Family (American International Journal of Biology and Life Sciences, 2020)
A diverse range of active therapeutic constituents i.e. antioxidants from medicinal plants of Solanaceae family are responsible for anticancer & antibacterial activity. The study was aimed to investigate phytochemicals i.e. alkaloids, phenols, tannins, flavonoids, saponins, glycosides, and steroids qualitatively in selected plants of Solanaceae family. Total phenolic and flavonoid content of the aqueous extracts of the plants were determined quantitatively by the Folin-Ciocalteus reagent method and modified Aluminium Chloride assay respectively.Flavanoids present in the extracts of Solanumnigrum(fruit and leaf), Daturainoxia (leaf) and Capsicum annum (fruit) samples were 0.39 ± 0.030, 0.42 ± 0.020, 0.51 ± 0.04, 0.34± 0.030µgmL-1 respectively, whereas phenolic contents were 94± 1.2, 107± 1.5, 96± 1.3, 87± 1.9 mg chlorogenic acid equivalent respectively. The aqueous and ethanolic extracts of S. nigrum, D. inoxia and C. annum showed bactericidal activity against strains of Salmonella typhimurium, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia and Staphylococcus aureus with (MIC)2mgmL-1 and 5mgmL-1. Highest free radical scavenging of DPPH activity 81.3% was exhibited by 2mgmL-1methanolic extract of D. inoxia. Docking of Murine with Saponin, Flavone, phenol showed hydrogen bond of length 2.47 Å, 1.98 Å, 2.285 Å respectively while two H-bonds with 1.96 and 2.56 Å bond lengths of alkaloids. Representative trends and in silico assay results explain the synergism among flavonoids, alkaloids, and phenols. The phytochemicals provide antibacterial activity, antioxidant property as well as anti-cancerous bioactive compounds such as alkaloids and tannins, justifying their therapeutic efficacy in the field of cancer medicine.